2021
DOI: 10.1080/08923973.2021.1939371
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic acid, as an inhibitor of HMGB1, alleviates bleomycin-induced pulmonary toxicity in mice through the MAPK and Smad3 pathways

Abstract: Aim: High-mobility group box 1 (HMGB1) protein has been noticed particularly for its pivotal role in several pathologies. However, the relevance between HMGB1 and pathological progress in lung toxicity still remains unclear. In the study, we evaluated the effect of glycyrrhizic acid as an HMGB1 inhibitor on the early inflammation and late fibrosis in bleomycin-induced pulmonary toxicity in mice. Methods: We established a bleomycin-induced pulmonary toxicity model to detect the relevance between HMGB1 and patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Among the inhibitors targeting HMGB1, glycyrrhizic acid is the most widely used and the most effective, so this study chose glycyrrhizic acid as an intervention to explore its intervention effect and mechanism on experimental silicosis in mice. Studies have shown that HMGB1 exists in the early stages of pulmonary inflammation and late fibrosis, and glycyrrhizic acid inhibits the expression of HMGB1, which can slow down the progression of pulmonary inflammation and fibrosis [ 15 ]. Glycyrrhizic acid can not only inhibit SMAD2 and SMAD3 pathways mediated by TGF-β1 [ 39 ], but can also change the pathological morphology of the bile duct ligation model and prevent liver fibrosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the inhibitors targeting HMGB1, glycyrrhizic acid is the most widely used and the most effective, so this study chose glycyrrhizic acid as an intervention to explore its intervention effect and mechanism on experimental silicosis in mice. Studies have shown that HMGB1 exists in the early stages of pulmonary inflammation and late fibrosis, and glycyrrhizic acid inhibits the expression of HMGB1, which can slow down the progression of pulmonary inflammation and fibrosis [ 15 ]. Glycyrrhizic acid can not only inhibit SMAD2 and SMAD3 pathways mediated by TGF-β1 [ 39 ], but can also change the pathological morphology of the bile duct ligation model and prevent liver fibrosis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizic acid is an HMGB1 inhibitor [ 14 ], which is approved by FDA to treat hepatitis. Some studies have shown that HMGB1 exists in the early stage of pulmonary inflammation and late fibrosis, and glycyrrhizic acid inhibits the expression of HMGB1, which limits the progress of pulmonary toxicity [ 15 ]. Previous studies have shown that glycyrrhizin inhibits HMGB1 and thus inhibits EMT by blocking the downstream Smad2/3 signal pathway [ 16 ], but there is no study on glycyrrhizic acid in silica-induced silicosis in mice.…”
Section: Introductionmentioning
confidence: 99%
“…By suppressing signaling through the Smad3 and MAPK pathways, for example, glycyrrhizin (30 and 100 mg/kg for a period of 28 days, i.g.) has been shown to reduce the severity of bleomycin-induced inflammation and pulmonary fibrosis in mice ( 49 ). Glycyrrhizin (10 mg/kg for once every day in the first 3 weeks following by given once every 3 days until the twelfth week, intra-articular knee injection) treatment can also alleviate inflammation and the degeneration of cartilage tissue in a rat model of osteoarthritis via regulating the TLR4/NF-κB and HMGB1 pathways ( 50 ).…”
Section: The Impact Of Herbal Medicines On Glucocorticoid- Induced Osteoporosismentioning
confidence: 99%
“…The biological activity of glycyrrhizin is primarily associated with anti-inflammatory, anti-allergic, hepatoprotective, antitumor and antiviral effects [ 163 ]. The anti-inflammatory effect of glycyrrhizin is expressed by inhibition of high mobility group box chromosomal protein 1 (HMGB1) [ 164 ]. In the acute phase of stroke, stimulation of the effectors of the innate immune response responsible for the removal of dead cells is observed.…”
Section: Natural Compoundsmentioning
confidence: 99%